2022
DOI: 10.1093/braincomms/fcad017
|View full text |Cite
|
Sign up to set email alerts
|

The motor system is exceptionally vulnerable to absence of the ubiquitously expressed superoxide dismutase-1

Abstract: Superoxide dismutase-1 is a ubiquitously expressed antioxidant enzyme. Mutations in SOD1 can cause amyotrophic lateral sclerosis, probably via a toxic gain of function involving protein aggregation and prion-like mechanisms. Recently, homozygosity for loss-of-function mutations in SOD1 has been reported in patients presenting with infantile onset motor neuron disease. We explored the bodily effects of Superoxide dismutase-1 enzymatic deficiency in eight children homozygous for the p.C112Wfs*11 truncating mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In order to investigate whether oxidative stress affect mast cell degranulation in skin aging-related alterations and whether endogenous antioxidants are sufficient to counteract skin cell stress injury, we evaluated levels of both ROS and SOD-1, a ubiquitously expressed antioxidant enzyme. 62 We observed that skin ROS levels were more pronounced in elderly specimens when compared to adult specimens (Fig. 2A).…”
Section: Resultsmentioning
confidence: 75%
“…In order to investigate whether oxidative stress affect mast cell degranulation in skin aging-related alterations and whether endogenous antioxidants are sufficient to counteract skin cell stress injury, we evaluated levels of both ROS and SOD-1, a ubiquitously expressed antioxidant enzyme. 62 We observed that skin ROS levels were more pronounced in elderly specimens when compared to adult specimens (Fig. 2A).…”
Section: Resultsmentioning
confidence: 75%
“…Fortunately for SOD1 familial ALS (fALS) patients, the intrathecally administered antisense oligonucleotide that reduces synthesis of the SOD1 protein 41 , 75 , 76 was recently approved by the US Food and Drug Administration (FDA). While downregulation of SOD1 can be effective in SOD1 fALS, its long-term effects must be carefully monitored so that the protein does not reach a critically low expression level, 77 , 78 , 79 and, for all other forms of fALS/sALS, efficient disease modifying therapies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Disordered proteins are efficiently recognized for degradation and there is no synthesis of new protein. As a result, the amounts of mutant SOD1 in erythrocytes vary widely depending on the degrees of destabilization, from close to the wildtype protein to <0.1% (Ezer et al, 2022; Jonsson et al, 2002; Park et al, 2023; Sato et al, 2005). The remaining mutant SOD1 protein is likely to mostly be active, resulting in SOD1 activities in heterozygotes varying from half to equal of controls (Keskin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further emphasizing the importance of SOD1 activity and indicating vulnerability to low SOD1 levels in the CNS is the recent discovery of children homozygous for SOD1 mutations that result in total-loss-of enzymatic function. These children are born normal but develop, from about the age of 6 months, the Infantile SOD Deficiency Syndrome (ISODDES) with progressive affection of both the upper and lower motor neuron systems but also with additional neurological and hematological abnormalities (Andersen et al, 2019; Çakar et al, 2023; de Souza et al, 2021; Dogan et al, 2024; Ezer et al, 2022; Park et al, 2023). So far, homozygosity for four SOD1 mutations has been associated with causing ISODDES.…”
Section: Discussionmentioning
confidence: 99%